Profile of Macrosomic Babies at a Tertiary Level Hospital - Shah, Subhash Chandra; Shrestha, Devendra; Dhakal, Ajaya Kumar; Shakya, Arati; Shakya, Henish; Pradhan, Amita (Journal of Nepal Paediatric Society, 2016)
Introduction: Macrosomia is known to be associated with adverse neonatal outcomes. The aim of this study was to estimate the incidence of macrosomia in a tertiary teaching hospital of Nepal based on local intrauterine foetal growth percentile curve according to gestational age, risk factors for morbidity and mortality and neonatal outcome of macrosomia. Materials and Methods: This was a descriptive observational study done on live term macrosomic babies delivered during the study period at KIST Medical College Teaching Hospital, Lalitpur Nepal. The maternal and neonatal records of macrosomic babies were reviewed. All the macrosomic babies were followed up till discharge. Macrosomic babies needing admission into the neonatal care unit were considered as ones with complication. Maternal and neonatal risk factors associated with neonatal complications were analysed. Results: Among total of 2922 live singleton deliveries, 342 (11.7%) babies were macrosomic. The neonatal complications associated with macrosomia were seen in 19.6%. The risk factors significantly associated with neonatal complications were mode of delivery via caesarean section, instrumental delivery and 1 min low Apgar score. Maternal diabetes leading to macrosomia however was seen in only one case. The most common neonatal complications were neonatal sepsis (11.4%), significant hyperbilirubinaemia (2%) and transient tachypnoea of newborn (1.6%). Conclusions: Neonatal sepsis was the major cause of morbidity even in the macrosomic babies. Importance of early interventions for prevention and management of macrosomic babies with neonatal sepsis needs to be emphasized. J Nepal Paediatr Soc 2015;35(2):135-140